Measuring pH of skim milk and milk permeate at ultra-high temperatures at laboratory and pilot scale. (April 2023) - Aydogdu, Tugce; O'Mahony, James A.; Huppertz, Thom; Magan, Jonathan B.; McCarthy, Noel A.
Abstract: Changes in the pH of skim milk and skim milk ultrafiltration permeate on heating from 25 to 140 °C were examined. Results showed that the decrease in pH with increase in temperature up to 140 °C was not linear. Hydrogen ion release due to changes in the milk mineral balance were responsible for the reduction in pH with increase in temperature. The presence of milk proteins offered little buffering against the drop in pH. The precipitation of calcium phosphate resulted in sediment in milk permeate heated above ∼70 °C, but this did not occur in skim milk, with the pH remaining lower in milk permeate after heat treatment when measured at 25 °C. This study has shown that in-line pH measurements of milk at ultra-high temperatures is feasible, and could prove useful at laboratory and pilot-scale for studying interactions within, and stability of, more complex formulations with added minerals.